Ultra wide band (UWB) modulation for signal acquisition from biomedical implants - Mohammed, Mokhaled M. (Internationa Islamic University Malaysia, 2013)
A circuit for Ultra-Wide-Band (UWB) pulse generation, shaping and modulation is proposed. The circuit is optimized, in terms of component values, to facilitate fabrication in 0.13μm CMOS technology. The circuit is designed to satisfy the main application limitations and constraints. These constraints are in the form of low voltage, low bit error rate, and adherence to FCC spectral emissions mask. The technique used is simple, and capable of producing UWB pulses complying with the Federal Communication Committee (FCC) power spectral mask regulations. The performance of conventional modulation techniques is compared to the Pulse Interval Modulation (PIM) used in this work for its preferential performance parameters, which is meant to be of high utility for extracting data signals from bio-medical implants.